Age-Inclusive ICT Innovation for Service Delivery in South Africa: A Developing Country Perspective - Roos, Vera; Hoffman, Jaco (Springer Nature, 2022)
This is an open access book Considers user competence, context, and mediating influences on ICT innovation in a developing country context Presents baseline data of older South Africans' ICT use, with templates and examples Ties together discussions on low-cost technology development with sustainability goals